2010
DOI: 10.1016/j.jconrel.2010.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibacterial nanofibrous PLLA scaffolds

Abstract: In order to achieve high local bioactivity and low systemic side effects of antibiotics in the treatment of dental, periodontal and bone infections, a localized and temporally controlled delivery system is crucial. In this study, a three-dimensional (3D) porous tissue engineering scaffold was developed with the ability to release antibiotics in a controlled fashion for long-term inhibition of bacterial growth. The highly soluble antibiotic drug, Doxycycline (DOXY), was successfully incorporated into PLGA nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 40 publications
0
62
0
4
Order By: Relevance
“…Infection is caused by either bacterial colonization at the wound site or foreign body response resulting from the implant material [5].Antibacterial biomaterials are one of the greatest interests in the war against implant-related infections, representing the broadest group of anti-infective biomaterials [6]. Focal antibacterial drug-loaded biomaterials can deliver a desired drug dose directly to the infected site for an extended time period while minimizing systemic distribution of toxic drugs [7,8]. Infection associated with GTR/GBR implant is mainly caused by anaerobic bacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Infection is caused by either bacterial colonization at the wound site or foreign body response resulting from the implant material [5].Antibacterial biomaterials are one of the greatest interests in the war against implant-related infections, representing the broadest group of anti-infective biomaterials [6]. Focal antibacterial drug-loaded biomaterials can deliver a desired drug dose directly to the infected site for an extended time period while minimizing systemic distribution of toxic drugs [7,8]. Infection associated with GTR/GBR implant is mainly caused by anaerobic bacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al 65 reported a three-dimensional (3D) porous tissue engineering scaffold, which was able to release antibiotics in a controlled fashion for long-term inhibition of bacterial growth. A highly soluble antibiotic, doxycycline (DOXY), was incorporated into PLGA nanospheres (NSs) using a water-in-oil-in-oil (w/o/o) emulsion method.…”
Section: Infection and Inflammatory Bone Diseasesmentioning
confidence: 99%
“…The successful incorporation of DOXY onto 3D scaffolds and its controlled release from scaffolds suggests that the usage of nanofibrous scaffolds in the delivery of large molecules (such as growth factors) to the delivery of small hydrophilic drugs allows for a broader application and a more complex tissue engineering strategy. 65 Similarly, PLGA was employed to compose a poly (ethylene glycol) monomethyl ether (mPEG) and PLGA copolymer as a sol-gel drug delivery system for treating osteomyelitis. 66 This delivery system was shown to have several advantages in treating osteomyelitis, including easy preparation, 100% encapsulation rate, near-linear sustained release of drugs, injectable design, and in situ gelling of the target tissue.…”
Section: Infection and Inflammatory Bone Diseasesmentioning
confidence: 99%
“…43 Üç boyutlu nanoküreli PLLA iskelenin, bakteriyal gelişimin inhibisyonu için doksisilinin kontrollü olarak salınım kabiliyetini değerlendiren bir çalışmada, makroporöz ve nanofibröz yapıların iyi derecede birleştiği, 6 haftadan daha uzun zamanda bakteriyel gelişimi baskıladığı gösterilmiş ve böylece nanoküre iskele sistemlerinin protein ve ilaç moleküllerinin taşınması ile doku mühendisliği uygulamalarında kullanılabileceği bildirilmiştir. 44 …”
Section: Sentetik Polimer İskelelerunclassified